Outcome of Non-small Cell Lung Cancer Patients With N3 Stage: Survival Analysis of Propensity Score Matching With a Validated Predictive Nomogram - Han, Chang; Wu, Yijun; Sun, Xu; Chong, Yuming; Kang, Kai; Liu, Zhikai; Zhang, Fuquan (Frontiers in Surgery, 2021)
Background and objectives: N3-positive non-small cell lung cancer (NSCLC) is usually regarded as inoperable. There were very few studies that focused on N3-NSCLC patients. This study aims to analyze prognosis of NSCLC patients with N3 disease and provides retrospective indications. Methods: NSCLC patients staged as N3 were retrospectively reviewed from the Surveillance, Epidemiology, and End Results database. Univariate and multivariate Cox regression were used for identifying prognostic factors. The selected predictive parameters by the least absolute shrinkage and selection operator (LASSO) regression were used to develop predictive nomogram models for overall survival (OS) and lung cancer-specific survival (CSS). The C-index values were calculated to assess the models’ predictive ability, while calibration curves were plotted to evaluate the agreement between the predicted and the actual survival. Survival curves were plotted by Kaplan-Meier method and were compared by log-rank test. Propensity score matching (PSM) was used to balance the baseline characteristics between treatment groups. Results: A total of 24747 N3-NSCLC patients were enrolled. The 1-year, 3-year and 5-year OS rates were 35.8%, 6.8% and 1.7%, while the corresponding CSS rates was 36.6%, 6.9% and 1.8%, respectively. The nomogram models were developed using 11 significant prognostic parameters, including age, sex, race, histology, stage, T stage, bone, brain and liver metastases, surgery and chemotherapy. Both of them demonstrated great predictive ability and performed well in the calibration curves. After PSM, patients receiving surgery demonstrated significantly better survival than those who did not for both IIIB-N3 and IV-N3 patients. For IIIB patients, chemotherapy plus radiation demonstrated significantly better survival than only chemotherapy. However, it seemed that the additional radiotherapy did not increase survival benefits to IV-N3 patients receiving chemotherapy. Conclusions: The nomogram models for predicting survival outcome of N3-NSCLC patients can be clinically used. Surgery may be beneficial to the survival for both IIIB_N3 and IV_N3, while radiotherapy may have additional survival benefits only in IIIB-N3 patients receiving chemotherapy.